PENDAMPINGAN KEGIATAN OPTIMALISASI TEKNOLOGI INFORMASI DALAM MENDUKUNG PROSES PENDIDIKAN DI TAMAN KANAK-KANAK - Muhammad Sholeh; Yuliana Rachmawati; Dina Andayati (LP2M Universitas Ibrahimy, 2022)
The use of information technology in supporting the learning process has become one of the needs that must be prepared by teachers. Teachers must adapt to the development of information technology. Teachers must adapt and adapt to children who use information technology more and are smarter in using smartphones. There are many applications that can be used to support the information technology-based learning process. One application that can be used in making online questions is to use the Wordwall application. The purpose of this activity is to provide alternatives to teachers in using applications to create online practice questions. The selection of the Wordwall application with the consideration that the application is easy to use and the questions presented to students can be chosen in the form of games. By packing in the game, it is hoped that students will feel happy in doing the questions. The method in the activity is carried out by providing training and practicing directly. The use of this practical method is expected that teachers can directly implement the making of questions. As a result of this activity, the teachers were able to develop online questions and form the outputs of the questions with various forms of games and distribute the questions to students.